Improving Students' Abilities by Developing an Inquiry Learning Model - Lalu Surya Jagat; Selamet Riadi; Idham; Runi Fazalani (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This research aims to improve students' knowledge and thinking abilities by developing an inquiry learning model. The method used by the researcher is qualitative, which describes something in the form of writing. In addition, the Inquiry also teaches students to think critically, namely by giving opinions and using reason when deciding something or what is being discussed. It also concerns the potential of students to learn by involving critical thinking or inquiry learning. This research shows that learning based on the Quran must be applied because this will make it easier for teachers or prospective teachers in the teaching and learning process. In addition, by learning the Quran, students can be active in the classroom and think logically.